2018
DOI: 10.21475/ajcs.18.12.03.pne619
|View full text |Cite
|
Sign up to set email alerts
|

Soybean growth, solar energy conversion and seed vigour affected by different nitrogen (N) doses

Abstract: The objective of this study was to evaluate soybean growth, conversion of solar energy and seed vigour of plants cultivated with different nitrogen doses. We carried out experiments using the cultivar BMX Potência RR belongs to the maturation group 6.7, presenting an indeterminate growth habit. The experimental design was completely randomised with four replications in a 4 x 8 factorial scheme (four nitrogen doses and eight collection periods). In the Vn stage of soybean development, we applied four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
3
1
Order By: Relevance
“…The vigor evaluated through the tetrazolium test revealed a positive effect resulting from the application of N in all treatments, with increments of up to 6.7%, if compared to the absence of N in coverage. In this sense, the results of this research corroborate those found by Aisenberg et al (2018), who, when evaluating the vigor by the seedling emergence velocity index, found out that seedlings from seeds under the influence of the application of N at the dose of 50 kg ha -1 reached higher values in 16.5, 11.4 and 19.1%, when compared to those under 0, 25 and 75 kg ha -1 of N, respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The vigor evaluated through the tetrazolium test revealed a positive effect resulting from the application of N in all treatments, with increments of up to 6.7%, if compared to the absence of N in coverage. In this sense, the results of this research corroborate those found by Aisenberg et al (2018), who, when evaluating the vigor by the seedling emergence velocity index, found out that seedlings from seeds under the influence of the application of N at the dose of 50 kg ha -1 reached higher values in 16.5, 11.4 and 19.1%, when compared to those under 0, 25 and 75 kg ha -1 of N, respectively.…”
Section: Resultssupporting
confidence: 90%
“…For the emergence of seedlings in beds, all kinds of management with the application of N in coverage, regardless of the application stage, presented higher emergency values than 0R2/0R5, with increments of up to 5.2%, when the application of N was split between stages R2 and R5 (60R2/60R5). These results were lower than those observed by Aisenberg et al (2018), who observed increments of 12, 15 and 10% in the emergence of seedlings, for seeds from plants subjected to applications of 25, 50, and 75 kg of N ha -1 , respectively, and compared to the absence of N in coverage. In the same study, the emergence of seedlings presented a quadratic response to the different doses of N evaluated, with maximum emergence of seedlings at the estimated dose of 47.3 kg of N ha -1 , with a decreasing tendency for doses higher than this.…”
Section: Resultscontrasting
confidence: 80%
“…However, the values of the electrical conductivity test presented in the same table, infer that without application, an application and two applications treatments that do not differ statistically from each other, present statistical difference in relation to treatments three applications, four applications and five applications.Through the electrical conductivity data (Table 3) correlated with PMS and germination (Table 1), it can be inferred that the seeds that received the highest number of fungicide application had higher quality. This is justified by the fact that the increase of leachate solutes is directly related to the decrease in seed germination and vigor (Binotti et al, 2008;Aisenberg et al, 2018). Similar results were found by Pinto et al (2011), who did not observe a difference between the treatments for the accelerated aging test, and also found that seeds that did not receive fungicide application for the control of Asian rust obtained higher leaching of solutes, being considered of lower physiological quality.…”
Section: Resultsmentioning
confidence: 55%
“…These groups act with different modes of action, distinct sites of action in pathogens, improve disease control and maintain the photosynthetic area of plants over time. Carboxamide is a specific site fungicide that acts on the inhibition of the enzyme Succinate dehydrogenase, this new chemical group showed better results than the other chemical groups in the control of Phakopsorapachyrhizi (Embrapa, 2014;Zanatta et al, 2018;Aisenberg et al, 2018). Dithiocarbamates are multi-site fungicides that act on several processes vital to pathogens, being an excellent tool to increase the efficiency of systemic fungicides and disease management (Silva, 2015;.…”
Section: Effect Of Fungicidesmentioning
confidence: 99%